PENGARUH TEKNOLOGI INFORMASI DAN PENGENDALIAN INTERNAL TERHADAP KUALITAS SISTEM INFORMASI AKUNTANSI MANAJEMEN PADA BANK CENTRAL ASIA - Rosdianti, Siti (Accounting Study Program, Faculty of Economics and Business, Langlangbuana University Bandung, 2018)
This research aims to analyze the influence of information technology and internal controls of the quality of accounting information system management in Bank Central Asia, Tbk KCP Batununggal Bandung. The research of using primary data obtained through the dissemination of the questionnaire to the 40 respondents, then to a question in the questionnaire is divided into three categories. That where there are 6 questions about information technology, 4 regarding internal control, as well as 9 questions about management accounting system. In this study the employees of PT Bank Central Asia, Tbk KCP Batununggal serve as the object of research. Methods of analysis used consists of the type of analysis, the descriptive analysis and structural equation modeling through Analysis (Structural Equation Modeling – SEM). Data that have been obtained are then processed using the SPSS program 23.0 For Windows. The results of the research showed that information technology and internal controls is very influential to the quality of the accounting information system management in Bank Central Asia, Tbk KCP Batununggal Bandung.